Penyisihan Warna Dan Zat Organik (KMnO4) Pada Air Gambut Dengan Biokoagulan Gel Lidah Buaya - Yawaritsa Yawaritsa; Syarfi daud; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Peat water in quantitative subject is very potential to be proceed for cleaned water in water resources. But in qualitative aspect, there is so much problem, there are the colour (dark brown), low PH, and high organic inside. The using of Biocoagulan is the best way as alternative for decrease the using of sintetic coagulant that can influence our health for a long term use. The purpose of this experiment is for knowing the effect of dosage (V/V), speed of stirring, and PH for decreasing colour and organic substances (KMnO4) in peat water with using biocoagulant aloevera gel. The variation are dosage of aloe vera gel (10 mL/L, 15mL/L, 20 mL/L ), the speed of stirring (100 rpm ,150 rpm and 200 rpm) with the PH constantly in the nature of PH peat water it self and PH 7. The result show that peat water treatment with using aloe vera gel with variation 15 ml/l, speed of stirring 200 and PH7 is the best result for decreasing the colour with value 80,66 % and organic substances is about 69,69% Keywords : Peat Water, Stirring Speed, Coagulation-Floculation, Biocoagulant, Aloe Vera